Comparing the Broad Socio-cognitive Profile of Youth with Williams Syndrome and 22q11.2 Deletion Syndrome - Weisman, Omri (J Intellect Disabil Res, 2017)
BACKGROUND: Numerous studies have assessed the socio-cognitive profile in Williams syndrome (WS) and, independently, in 22q11.2 deletion syndrome (22q11.2DS). Yet, a cross-syndrome comparison of these abilities between individuals with these two syndromes with known social deficits has not been conducted. METHODS: Eighty-two children participated in four study groups: WS (n=18), 22q112.DS (n=24), age-matched individuals with idiopathic developmental disability (IDD; n=20), and typically developing (TD) controls (n=20). Participants completed four socio-cognitive tests; facial emotion recognition, mental state attribution, differentiating real from apparent emotions, and trait inference based on motives and actions-outcomes. RESULTS: The current findings demonstrate that children with WS were better in labeling happy faces compared to children with 22q11.2DS, partially reflecting their exaggerated social drive. In the false belief task, however, the WS and IDD groups performed poorly compared to the 22q11.2DS group, possibly due to their difficulty to interpret subtle social cues. When asked to identify the gap between real-negative vs. apparent-positive emotions, the 22q11.2DS group performed similarly to TD children but better than the WS group, possibly due to their anxious personality and their innate bias towards negatively-valence cues. Finally, individuals with WS were more willing to become friends with a story-character even when the character’s motives were negative, reflecting their difficulty to avoid potentially harmful real-life situations. CONCLUSIONS: Overall, our multi-facet socio-cognitive battery uncovered strengths and weaknesses in social cognition that are syndrome-specific, shared among the genetic syndromes, or common to the three clinical groups compared to healthy controls. Our findings underscore the need to devise age- and condition-specific assessment tools and intervention programs toward improving these children’s socio-cognitive deficits.